2016
DOI: 10.1007/s13277-016-5113-z
|View full text |Cite
|
Sign up to set email alerts
|

Yeast two-hybrid screening identified WDR77 as a novel interacting partner of TSC22D2

Abstract: Transforming growth factor β-stimulated clone 22 domain family, member 2 (TSC22D2), a member of the TSC22D family, has been implicated as a tumor-associated gene, but its function remains unknown. To further explore its biological role, yeast two-hybrid screening combined with multiple bioinformatics tools was used to identify 44 potential interacting partners of the TSC22D2 protein that were mainly involved in gene transcription, cellular metabolism, and cell cycle regulation. The protein WD repeat domain 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Notably, KEGG pathway enrichment analysis suggested significant enrichment in pathways including ECM-receptor interaction, microRNA in cancer [45][46][47][48] and PI3K-Akt signaling pathway. The previous studies reported that PI3K-Akt signaling activation is associated with tumor cell growth, proliferation, migration and angiogenesis of TGCT [49][50][51][52]. It is well known that increased cell proliferation and migration are the leading causes for malignant tumor initiation and progression [53][54][55], thus our biological analysis results were consistent with previous researches.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, KEGG pathway enrichment analysis suggested significant enrichment in pathways including ECM-receptor interaction, microRNA in cancer [45][46][47][48] and PI3K-Akt signaling pathway. The previous studies reported that PI3K-Akt signaling activation is associated with tumor cell growth, proliferation, migration and angiogenesis of TGCT [49][50][51][52]. It is well known that increased cell proliferation and migration are the leading causes for malignant tumor initiation and progression [53][54][55], thus our biological analysis results were consistent with previous researches.…”
Section: Discussionsupporting
confidence: 91%
“…Mining of published high-throughput data is a commonly used and low-cost method for identifying novel biomarkers and gaining insight into the biological functions of novel genes [2123]. To identify potential novel functions of AFAP1-AS1 , we downloaded a GEP dataset, GSE12452, from the GEO database; this dataset consists of 41 samples of whole-genome GEP data, including 10 samples of non-tumor nasopharyngeal epithelial (NPE) biopsies and 31 cases of NPC [24].…”
Section: Resultsmentioning
confidence: 99%
“…Tissue RNA isolation and amplification were performed as our laboratory described previously 24-26. Cell RNA was extracted using TRIzol reagent (Invitrogen, Carlbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The bottom well contained growth medium with 20 % FBS. Cells were incubated at 37°C for 24 h. After 24 h, the cells that had migrated to the lower face of the filters were fixed with 100% methanol and stained with 0.5% crystal violet and counted 24, 25.…”
Section: Methodsmentioning
confidence: 99%